Communication Approaches for Khanom La Story in the Situation of the Covid - 19 Pandemic - Chamnian, Korrakot; Chamnian, Methawee; Kuenui, Panjaporn; Mukharak, Thongphun; Boonkwan, Sasipat; Sriharan , Parichat; Sampim, Tatcha (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The purposes of the research were to 1. study the situation of the distribution of Kanom La Products, Nakhon Si Thammarat Province during the Covid - 19 pandemic. and 2. to propose approaches for communicating the story of Khanom La in the situation of the Covid - 19 pandemic. This qualitative research was conducted and obtained data from key informants who are 5 groups of Khanom La entrepreneurs in Nakhon Si Thammarat Province. They were recruited using purposive sampling technique. The instrumentation consisted of interviews and observations and content analysis was applied during data analysis. The research findings showed that 1. the distribution of Khanom La Products, Nakhon Si Thammarat Province was affected during the pandemic of Covid - 19. This made the decline in products distribution, and 2. in order for entrepreneurs to communicate the story of Khanom La to stimulate distribution during the pandemic of COVID - 19, the approaches consist of product communication approach which presents highlight and identity stories of Khanom La in each area, social media approach, using various content approach, using both still images and motion pictures approach, communicating with continuity approach and developing marketing communication skills for entrepreneurs of Khanom La approach.